A fog‐based collaborative intrusion detection framework for smart grid. Issue 2 (11th March 2020) - Li, Wenjuan; Au, Man Ho; Wang, Yu
Summary: With the rapid development of information and communication technologies (ICTs), the conventional electrical grid is evolving towards an intelligent smart grid. Due to the complexity, how to protect the security of smart grid environments still remains a practical challenge. Currently, collaborative intrusion detection systems (CIDSs) are one important solution to help identify various security threats, through allowing various IDS nodes to exchange data and information. However, with the increasing adoption of ICT in smart grid, cloud computing is often deployed in order to reduce the storage burden locally. However, due to the distance between grid and cloud, it is critical for smart grid to ensure the timely response to any accidents. In this work, we review existing collaborative detection mechanisms and introduce a fog‐based CIDS framework to enhance the detection efficiency. The results show that our approach can improved the detection efficiency by around 21% to 45% based on the concrete attacking scenarios. Abstract : We propose a fog‐based collaborative intrusion detection system (CIDS) framework to help reduce the latency caused by the distance between smart grid (SG) and cloud. In the evaluation, we simulate a smart grid environment and investigate our framework under both internal and external attacks. The results show that our approach can improved the detection efficiency by around 21% to 45% based on the concrete attacking scenarios.